2005
DOI: 10.1097/01.prs.0000154208.67390.5c
|View full text |Cite
|
Sign up to set email alerts
|

The Facial Artery Perforator Flap for Reconstruction of Perioral Defects

Abstract: The facial artery perforator flap offers a versatile tailor-made flap, because of the reliable presence of perforators, with a large arc of rotation and an aesthetically pleasing donor site. The thin pedicle makes it an ideal flap for one-stage reconstruction without secondary revisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 15 publications
0
78
0
1
Order By: Relevance
“…There are many reconstructive options for midface defects but the nasolabial flap and its many variations work well for nasal ala reconstruction and other facial defects 1,2 . Recently however, the use of FAP flaps for such reconstructive work is becoming increasingly common 2,6,8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many reconstructive options for midface defects but the nasolabial flap and its many variations work well for nasal ala reconstruction and other facial defects 1,2 . Recently however, the use of FAP flaps for such reconstructive work is becoming increasingly common 2,6,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the use of such flaps has facilitated the possibility of one-stage reconstruction instead of the traditional two-(or more) stage technique 1,2 . This has also been reported to provide a much better aesthetic result that is more appealing to the patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that there is a racial variation in the origin and the branches patterns of the facial artery (Koh et al, 2003;Nakajima et al, 2002;Niranjan, 1988). Facial vessels are widely used in plastic surgery as the pedicle of some flaps (D'Arpa et al, 2009;Hofer et al, 2005;Joshi et al, 2005;Pribaz et al, 1992;Yamauchi et al, 2010). The flap based on the facial artery could be originated from the proximal or distal portion of the artery.…”
Section: Introductionmentioning
confidence: 99%
“…The dissection is carried out in a plane above that of the muscles of facial expression. FAP flap can be as large as 5 × 5 cm and the donor defect can be closed primarily [2].…”
mentioning
confidence: 99%